Assessment of the Service Life of Reinforced Concrete and Steel Elements (Texas Journal of Engineering and Technology, 2022)
The article provides information on the service life of metal and reinforced concrete elements,their shelf life, assessment of the technical condition of damaged elements to increase their strength